2022
DOI: 10.1080/24725579.2022.2142866
|View full text |Cite
|
Sign up to set email alerts
|

A mask-guided attention deep learning model for COVID-19 diagnosis based on an integrated CT scan images database

Abstract: The global extent of COVID-19 mutations and the consequent depletion of hospital resources highlighted the necessity of effective computer-assisted medical diagnosis. COVID-19 detection mediated by deep learning models can help diagnose this highly contagious disease and lower infectivity and mortality rates. Computed tomography (CT) is the preferred imaging modality for building automatic COVID-19 screening and diagnosis models. It is well-known that the training set size significantly impacts the performance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…For the training and testing, we used two datasets, COVIDx CT-2 [ 11 , 12 ] and the integrated CT scan dataset [ 43 ]. The COVIDx CT-2 dataset has two diverse, large-scale datasets named COVIDx CT-2A and COVIDx CT-2B, and we chose COVIDx CT-2A.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the training and testing, we used two datasets, COVIDx CT-2 [ 11 , 12 ] and the integrated CT scan dataset [ 43 ]. The COVIDx CT-2 dataset has two diverse, large-scale datasets named COVIDx CT-2A and COVIDx CT-2B, and we chose COVIDx CT-2A.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To demonstrate the improved discriminative performance of the VGG19 model, we conducted training and testing on a moderately large dataset and compared it with the original VGG19, Nair et al [ 39 ], Chaudhary et al [ 40 ], Perumal et al [ 41 ], Garg et al [ 42 ], and Maftouni et al [ 43 ], as shown in Table 5 . The results presented in Figure 9 indicate that the improved VGG19 outperforms VGG19 in both CAP and COVID-19 categories, achieving a 4.77% higher recall rate.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures 1-3 showcase samples from the three datasets listed for each respective class. Curated COVID-CT (Maftouni et al, 2021), or COVID19 C, is a large lung CT dataset curated from seven different publicly available datasets. It comprises images of 7,593 COVID, 6,893 normal and 2,618 community-acquired pneumonia cases.…”
Section: Data Preparationmentioning
confidence: 99%